The Use of Sundanese Mother Tongue in Learning English - Fuzi Fauziyyah; Lidiyatul Izzah (Scripta : English Department Journal, 2022)
The use of mother tongue in English class has advantages and disadvantages. Therefore, this study was conducted to determine the function of the use of Sundanese language in learning English, as well as the views of students regarding the use of Sundanese language in English classes at MA Miftahussa'adah in grade 11 science and social studies. The methodology used in this study is a qualitative approach with a descriptive method. Data collection techniques in this study through observation, and interviews. The results showed: 1) The function of the use of the Sundanese mother tongue in learning English is as an introduction, explanation, expressing feelings or emotions and providing motivation, 2) Students have positive perception of the use of Sundanese in learning English. This study provides us with information about the use of mother tongue in the classroom. From the students we can see that the use of the mother tongue should not be completely eliminated but can only be minimized, this is to maintain the comfort of students in learning English. And so that students better understand well and easily the material taught by the teacher.